2022
DOI: 10.1080/17461391.2021.2023655
|View full text |Cite
|
Sign up to set email alerts
|

Lower impact forces but greater burden for the musculoskeletal system in running shoes with greater cushioning stiffness

Abstract: In a recent randomised trial investigating running shoe cushioning, injury risk was greater in recreational runners who trained in the shoe version with greater cushioning stiffness (Stiff) compared to those using the Soft version. However, vertical impact peak force (VIPF) was lower in the Stiff version. To investigate further the mechanisms involved in the protective effect of greater cushioning, the present study used an intra-subject design and analysed the differences in running kinematics and kinetics be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Notably, shoe type was included in the reference equation for only 3 of the biomechanical variables (VIP, time to VIP, and peak breaking force), consistent with previous findings. 19,22 As the participants were tested in 1 of the 2 study shoe versions (ie, greater or lower cushioning properties), 22 clinicians should consider the cushioning properties of the shoe that the patient is being tested in when performing gait analysis and record it as hard (eg, racing flat or minimalist shoe) or soft (eg, maximalist or highly cushioned shoe). Additional explanations on the use of the regression equations are provided in the spreadsheet (Supplemental Material 2).…”
Section: Reference Regression Equationsmentioning
confidence: 99%
“…Notably, shoe type was included in the reference equation for only 3 of the biomechanical variables (VIP, time to VIP, and peak breaking force), consistent with previous findings. 19,22 As the participants were tested in 1 of the 2 study shoe versions (ie, greater or lower cushioning properties), 22 clinicians should consider the cushioning properties of the shoe that the patient is being tested in when performing gait analysis and record it as hard (eg, racing flat or minimalist shoe) or soft (eg, maximalist or highly cushioned shoe). Additional explanations on the use of the regression equations are provided in the spreadsheet (Supplemental Material 2).…”
Section: Reference Regression Equationsmentioning
confidence: 99%
“…When considering the effects of midsole hardness on BRFs in general, ve studies found reduced peak rearfoot eversion in harder midsoles than in softer midsoles (42)(43)(44)(45)(46). However, four studies found unchanged peak rearfoot eversion angles when running in soft and hard midsoles (36, [47][48][49]. Four studies reported that different midsole hardness could not systematically affect rearfoot eversion range of motion (42,46,47,50).…”
Section: Midsole Compression Stiffness and Hardnessmentioning
confidence: 99%
“…However, four studies found unchanged peak rearfoot eversion angles when running in soft and hard midsoles (36, [47][48][49]. Four studies reported that different midsole hardness could not systematically affect rearfoot eversion range of motion (42,46,47,50). In contrast, one study found a reduction in rearfoot eversion range of motion in hard midsoles (49), and another study found that the range of motion of the rearfoot was lower when runners were running in softer midsoles (51).…”
Section: Midsole Compression Stiffness and Hardnessmentioning
confidence: 99%
See 2 more Smart Citations